Investigation of proton damage in III-V semiconductors by optical spectroscopy - Yaccuzzi, Exequiel Eliseo; Khachadorian, S.; Suárez, S.; Reinoso, María Elba; Goñi, A.R.; Strittmatter, A.; Hoffmann, A.; Giudici, Paula (American Institute of Physics, 2016)
Fil: Yaccuzzi, Exequiel. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina